2014
DOI: 10.5812/ircmj.19797
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Effects of Forearm Kinesio Taping on Grip Strength

Abstract: Background:Due to the fundamental role of gripping in most upper limb activities, grip strength promotion is a chief goal in the treatment of patients with upper limb musculoskeletal disorders. Kinesio taping is a novel and effective therapeutic technique believed to facilitate muscle contraction through stimulating mechanoreceptors and increasing the sensory feedback around the taped region.Objectives:The present study aimed to identify the best region (flexor, extensor and flexor/extensor regions) and time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 24 publications
(37 reference statements)
1
31
1
2
Order By: Relevance
“…However, results of the present study were in contrast to studies by Kuo et al [20], Mohammadi et al [10] and Thiago et al [21] who observed positive effects of kinesio taping on hand grip strength. Kuo et al [20] used facilitation and inhibition techniques of kinesio taping on maximal isometric strength of wrist and finger muscles.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…However, results of the present study were in contrast to studies by Kuo et al [20], Mohammadi et al [10] and Thiago et al [21] who observed positive effects of kinesio taping on hand grip strength. Kuo et al [20] used facilitation and inhibition techniques of kinesio taping on maximal isometric strength of wrist and finger muscles.…”
Section: Resultscontrasting
confidence: 57%
“…Mohammadi et al [10] aimed to identify the best region of forearm taping, effect timing on forearm muscles by measuring hand grip strength. They found extensor taping more effective than flexor taping and recommended kinesio taping to improve hand grip strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…El Kinesio Taping es una herramienta terapéutica utilizada mundialmente en el campo deportivo desde su creación en 1979 por el doctor Kenzo Kase; plantea que uno de sus objetivos en el tratamiento es brindar estabilidad a la articulación como una manera rápida de disminuir el dolor y la inflamación, como lo manifiesta Villota, (2014), "fue diseñado para facilitar el proceso de curación natural del cuerpo permitiendo apoyo y estabilidad a los músculos y las articulaciones sin restringir el alcance del movimiento del cuerpo"; dentro de los efectos fisiológicos se encuentran los descritos por Kouhzad Mohammadi et al, (2014) quien enuncia que "son el analgésico, el de aumento de la circulación linfática y sanguínea, reducción de la fatiga muscular y modulación del tono muscular, mejora la interrelación entre las fascias, actúa sobre la postura y la propiocepción articular".…”
Section: Introductionunclassified
“…The results of both immediate and long-term effects (10,11) are controversial, highlighting the need for further studies. In addition, the benefits of KT reported by users on a day-to-day technical application is unknown and without scientific and clinical evidence, raising the question of a possible "placebo effect" (12).…”
Section: Introductionmentioning
confidence: 99%